2005
DOI: 10.1152/jn.00532.2005
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Corticospinal Tract Function by Treadmill Training After Incomplete Spinal Cord Injury

Abstract: Thomas, Sarah L. and Monica A. Gorassini. Increases in corticospinal tract function by treadmill training after incomplete spinal cord injury. J Neurophysiol 94: 2844 -2855, 2005 First published July 6 2005. doi:10.1152/jn.00532.2005. In this study, we examined if several months of intensive locomotor training increases the function of spared corticospinal tract pathways after chronic spinal cord injury (SCI) in association with the recovery of locomotor function. Transcranial magnetic stimulation (TMS) at in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
152
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(165 citation statements)
references
References 45 publications
10
152
1
2
Order By: Relevance
“…This is not the first report of postintervention and specifically post treadmill training effects on corticomotor excitability using TMS in people with neuropathology. Changes in corticomotor excitability and associated improvements in walking function were found after intensive treadmill training both in people with spinal cord injury 57,58 and stroke. 59 However, to our knowledge, this is the first demonstration of exercise-induced changes in corticomotor excitability using TMS in individuals with PD, a progressive neurologic disorder.…”
Section: Discussionmentioning
confidence: 98%
“…This is not the first report of postintervention and specifically post treadmill training effects on corticomotor excitability using TMS in people with neuropathology. Changes in corticomotor excitability and associated improvements in walking function were found after intensive treadmill training both in people with spinal cord injury 57,58 and stroke. 59 However, to our knowledge, this is the first demonstration of exercise-induced changes in corticomotor excitability using TMS in individuals with PD, a progressive neurologic disorder.…”
Section: Discussionmentioning
confidence: 98%
“…86 A small imaging study with four subjects indicated increased activation in the cortical sensorimotor and cerebellar regions after locomotor training in both subacute and chronic, motor-incomplete SCI. 87 In a case report of an individual with chronic, motorincomplete SCI, locomotor training that emphasized feedback-error learning was associated with increases in somatosensory and corticospinal excitability, as well as radiographic evidence of increased corticospinal connectivity.…”
Section: Training-related Modulation Of Supraspinal Circuitsmentioning
confidence: 99%
“…What are the mechanisms of such improvements? Using motor evoked potentials induced by transcranial magnetic stimulation as an indicator of excitability changes of the corticospinal pathway, it was found that, after a period of treadmill locomotor training, corticospinal responses (Thomas and Gorassini, 2005) are increased and cortical-dependent muscle unit coherence is increased, suggesting a major role of the cortex in human rehabilitation. Although such supraspinal participation is certainly sine qua none to regain voluntary locomotor control (Yang and Gorassini, 2006), intrinsic spinal mechanisms are probably also of crucial importance in the proper expression of locomotion in humans as was shown in the cat (Barrière et al, 2007).…”
Section: A Synergy Between T-cell-based Vaccination and Adult Neural mentioning
confidence: 99%